2020
DOI: 10.5194/acp-20-4227-2020
|View full text |Cite
|
Sign up to set email alerts
|

Influences of oceanic ozone deposition on tropospheric photochemistry

Abstract: Abstract. The deposition of ozone to seawater is an important ozone sink. Despite constituting as much as a third of the total ozone deposition, it receives significantly less attention than the deposition to terrestrial ecosystems. Models have typically calculated the deposition rate based on a resistance-in-series model with a uniform waterside resistance. This leads to models having an essentially uniform deposition velocity of approximately 0.05 cm s−1 to seawater, which is significantly higher than the li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 35 publications
(65 reference statements)
3
37
0
Order By: Relevance
“…Incorporating such a deposition scheme into the UK Chemistry and Aerosol CCM (UKCA; Luhar et al, 2018) decreases ozone deposition over the ocean by almost half, which corresponds to a 10 % decrease in the model calculated total global ozone deposition. Similar results are obtained in a study with an updated surface ocean iodide distribution and the Luhar et al (2018) scheme with the GEOS-Chem chemical transport model (CTM;Pound et al, 2020). An overall downward revision of global ozone deposition rates can be expected as these rates are more widely adopted.…”
Section: Development Of Emissions Inventoriessupporting
confidence: 83%
“…Incorporating such a deposition scheme into the UK Chemistry and Aerosol CCM (UKCA; Luhar et al, 2018) decreases ozone deposition over the ocean by almost half, which corresponds to a 10 % decrease in the model calculated total global ozone deposition. Similar results are obtained in a study with an updated surface ocean iodide distribution and the Luhar et al (2018) scheme with the GEOS-Chem chemical transport model (CTM;Pound et al, 2020). An overall downward revision of global ozone deposition rates can be expected as these rates are more widely adopted.…”
Section: Development Of Emissions Inventoriessupporting
confidence: 83%
“…Tropospheric ozone is important due to its considerable effects on human health (Medina-Ramón et al, 2006), agricultural yields (Heck et al, 1982), and global warming (Stevenson et al, 2013). Dry deposition is a major sink of tropospheric ozone, comprising as much as 25 % of total loss from the troposphere (Ganzeveld et al, 2009;Lelieveld and Dentener, 2000;Pound et al, 2020). Deposition to the sea surface is the greatest source of uncertainty in global estimates Published by Copernicus Publications on behalf of the European Geosciences Union.…”
Section: Introductionmentioning
confidence: 99%
“…When a variable reaction-diffusion sublayer depth was considered as being proportional to the reactiondiffusion length scale (l m = √ D/a), Luhar et al (2018) found it necessary to multiply l m by a factor of 0.7 to obtain a δ m value that fitted reasonably with observations. Pound et al (2020) were however able to obtain a good fit to observational data without this factor by using the oceanic iodide parameterisation of Sherwen et al (2019) in place of that of Macdonald et al (2014). Pound et al (2020) define the reaction-diffusion layer depth according to Eq.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations